Penelusuran Minat dan Bakat Olahraga Pada Siswa Menengah Pertama Di Kabupaten Demak Tahun Pelajaran 2019/2020 (Indonesian Journal for Physical Education and Sport, 2021)
The The background of this research is the unknown talent scouting process with the sport search method, trainers and teachers lack understanding about scouting using the sport search method, there has never been a sport search talent scout test. The purpose of this study to determine the sports talent of junior high school students in Demak Regency in the academic year 2019/2020. This research approach uses quantitative descriptive methods. The technique of collecting data uses questionnaire, sport search talet test and documentation. The population in this study were junior high school students in Demak Regency. The sampling technique uses purposive sampling. Data analysis in this research uses descriptive presents. Data processing using the sport search software application. The results of data analysis, a total of 45 students 24,1% of test takers had an interest in accordance with their talents and 142 students or 75,9% of test takers had an interest that was not in accordance with their talents. The conclusion obtained is that junior high school students in Demak Regency have a variety of sports talents, but some of the potential is not in accordance with the interests of students. The suggestion from researchers is that the scouting and fostering talent process should be further improved to optimize student achievement. With this research, it is hoped that it will become a reference or alternative for the process of scouting and developing sports talent in Demak Regency and other areas. .